Withania coagulans Fruit Extract Reduces Oxidative Stress and Inflammation in Kidneys of Streptozotocin-Induced Diabetic Rats - Ojha, Shreesh (Hindawi Publishing Corporation, 2014)
The present study was carried out to investigate the changes in oxidative and inflammatory status in streptozotocin-induced diabetic rat's kidneys and serum following treatment with Withania coagulans, a popular herb of ethnomedicinal significance. The key markers of oxidative stress and inflammation such as inflammatory cytokines (IL-1β, IL-6, and TNF-α) and immunoregulatory cytokines (IL-4 and IFN-γ) were increased in kidneys along with significant hyperglycemia. However, treatment of four-month diabetic rats with Withania coagulans (10 mg/kg) for 3 weeks significantly attenuated hyperglycemia and reduced the levels of proinflammatory cytokines in kidneys. In addition, Withania coagulans treatment restored the glutathione levels and inhibited lipid peroxidation along with marked reduction in kidney hypertrophy. The present study demonstrates that Withania coagulans corrects hyperglycemia and maintained antioxidant status and reduced the proinflammatory markers in kidneys, which may subsequently reduce the development and progression of renal injury in diabetes. The results of the present study are encouraging for its potential use to delay the onset and progression of diabetic renal complications. However, the translation of therapeutic efficacy in humans requires further studies.